USA’s policies on fracking - Shrivastava, Bulbul (My University, 2017)
In the past decade, the United States’ oil and gas industry experienced an extraordinary boom, due to shale gas. Shale gas accounted for only 1.6% of total US natural gas production in 2000, 4.1% by 2005, and an astonishing 23.1% by 2010. This remarkable growth has spurred interest in exploring for shale gas resources elsewhere. The purpose of the study is how the rise of fracking in the USA has impacted its foreign policy towards climate change. An exploratory qualitative method, known as process-tracing was used, with the aim of providing evidence-based literature in order to explore the change in the USA’s domestic energy and climate policies; as well to see the change in its stance on climate change on the international platform. Some of the key concluding findings relate to the Obama Administration’s championing of the Clean Energy Act.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts(International Relations), 2017
Keywords: Hydraulic fracturing--Environmental aspects--United States; Hydraulic fracturing--United States; Shale gas industry--Environmental aspects--United States